Modified Group Chain Acceptance Sampling Plans (MGChSP) based on the Minimum Angle Method - Mohd Azri Pawan Teh; Nazrina Aziz; Zakiyah Zain (International Journal of Supply Chain Management, 2019)
The established modified group chain acceptance sampling plans (MGChSP) only considered the consumer’s risk when developing the plans and turned down the producer’s risk, which means the established MGChSP satisfied the consumer but not the producer. Based on the above problem, this article proposes the minimum angle method for the MGChSP as the method considers both risks (consumer’s and producer’s) simultaneously. In order to develop the proposed MGChSP, the generalized exponential distribution is chosen as its lifetime distribution, and the time truncated simulation is done. The simulation produces the optimal number of groups, at different values of specified design parameters. It turns out that the satisfies both parties, consumer and producer, while the number of groups for the established MGChSP only satisfied the consumer. For application purpose, failure time (in hours) for computer software is used in order to demonstrate the usage of MGChSP in the industry.